Impacts of Res-Generation and Demand Pattern on Net Transfer Capatity: Implications for Effectiveness of Market Splitting in Germany - Michael Bucksteeg; Katrin Trepper; Christoph Weber (University of Duisburg-Essen, Chair for Management Science and Energy Economics, 2014)
For the further development of an integrated European electricity market, congestion management mechanisms are one of the major market design issues. Against the background of increasing generation from RES and resulting congestions, an efficient management of network congestions is gaining importance especially in Germany. Introducing nodal pricing as the first best mechanism is not considered to be realistic for Germany in the nearer future. Yet the splitting of the German electricity market into several market zones will also improve congestion management. A key issue in the so-called market splitting is the determination of the net transfer capacity (NTC) between the market zones as it determines the effectiveness of market splitting as congestion management mechanism. We therefore develop an integrated approach to incorporate the effects of renewables feed-in, load pattern and cross border flows on NTCs. We conclude that the NTCs strongly depend on RES infeed and that this effect has to be considered when modelling alternative congestion management mechanisms like market splitting.
Keywords: Q40; Q47; Q49; 330; net transfer capacity; congestion management; market splitting